A comparative study of Schiff base chelating resins: synthesis, uptake of heavy metal ions, and thermal studies - Al-Yusufy, Fatma A.; Al-Qadasy, Mohammed Q.; Jamil, Yasmin M. S.; Al-Maydama, Hussein M.; Akeel, Moathe M. (Eclética Química, 2018)
Two new chelating resins (Rciaa91 and Rciaa73) with different compositional chelating groups and degree of cross-linking were prepared by free radical copolymerization of Schiff bases obtained from condensation reaction of cinnamaldehyde (ci) with anthranilic acid (aa) and 1,4-phenylenediamine (pn) monomers. The synthesized materials were characterized using CHN analyses, FTIR, 1H-NMR, and thermal analyses (TGA, DTA). Batch technique was applied, and the contact time, pH and initial concentration of the metal ions were investigated as factors affecting the uptake behavior. The results obtained indicated that the chelating resin with larger compositional ratio of chelating moieties and lower degree of cross-linking showed lower optimum reaction time and higher uptake affinity towards the metal ions Cu(II), Cd(II), Co(II), Zn(II), Hg(II), and Pb(II), under the same conditions. Both the chelating resins showed uptake behavior of the metal ions in the following order Hg2+ > Cu2+ > Zn2+>Pb2+>Co2+ > Cd2+ each metal at its optimum pH and at the same reaction time and ion concentration. The thermal degradation behavior and stability of the resins were investigated by using non-isothermal thermogravimetric analysis (TGA/DTG/DTA), at 10 °C min-1 heating rate and under nitrogen. The Coats-Redfern method was used to evaluate the kinetic and thermodynamic parameters (ΔG*, ΔH* and ΔS*) for the prominent degradation steps in the TGA curves at 450-660 °C range.